Removable dental prostheses for patients with Sjögren's syndrome - Binhuraib, Haitham Mohammed; Khuzaee, Ahmed Ibrahim; Alsubaiei, Abdulrahman Fahad; Alshamali, Abdulrahman Abdulaziz; Aljuman, Abdulaziz Saeed; Althagafi, Mohammed Matar; Alqahs, Mohammad Dh; Alghamdi, Omar Ali; Alghamdi, Raneem Saad; Almuhaythif, Muhannad Abdullah; Alsulami, Weaam Abdulaziz (International Journal Of Community Medicine And Public Health, 2024)
Sjögren's syndrome (SS) is a chronic autoimmune condition primarily affecting the salivary and lacrimal glands, leading to pronounced dry mouth (xerostomia) and dry eyes. These symptoms create unique challenges for SS patients requiring removable dental prostheses, as the lack of saliva significantly impacts the retention, comfort, and overall effectiveness of these devices. Without adequate saliva, prosthetic retention diminishes, and patients frequently experience issues such as mucosal irritation and increased susceptibility to infections. To address these issues, tailored material choices are critical in designing effective prosthetic solutions. Soft liners, moisture-retentive acrylics, and antimicrobial coatings are among the innovations improving both retention and comfort for SS patients. The aesthetic and functional outcomes of prosthetic solutions are also essential considerations. Enhanced retention mechanisms, such as implant-supported overdentures, not only improve masticatory performance but also aid in preserving the patient’s facial profile and lip support. Advanced materials offering translucency and color stability contribute to a more natural appearance, which is critical for patient satisfaction. The maintenance of these prostheses requires specific care routines to mitigate microbial buildup and tissue irritation. Specialized cleaning agents and salivary substitutes help maintain hygiene and reduce discomfort, while regular follow-up visits enable timely adjustments to accommodate tissue changes and extend the prosthesis lifespan. Implementing a comprehensive approach that considers material selection, functional and aesthetic outcomes, and maintenance strategies can greatly enhance the quality of life for SS patients. By understanding and addressing the specific needs associated with xerostomic conditions, dental professionals can provide prosthetic solutions that offer both reliability and comfort in this challenging context. Regular patient education and diligent care routines remain essential to ensure the long-term success and durability of removable dental prostheses for individuals with SS.